The Determinants of Capital Structure: Evidence from Malaysian Companies - Chin Fei Goh; Wan Ying Tai; Amran Rasli; Owee Kowang Tan; Norhayati Zakuan (International Journal of Supply Chain Management, 2018)
The aim of this study is to investigate the determinants of capital structure for Malaysian manufacturing companies. The studied subjects were 174 Malaysia manufacturing companies listed on Bursa Malaysia from year 2011 to year 2014. Firm fixed-effect with robust standard was used in data analysis to address the potential heterogeneity and endogeneity that arise from panel data. The analysis shows that firm profitability and non-debt tax shield are negatively related to firm leverage. On the other hand, several corporate governance mechanisms, namely, ownership concentration, separation of CEO-chairs, board independence, are not related to firm leverage. Liquidity, firm size and asset structure are also not related to firm leverage of manufacturing firms.